Analisis Kejadian Syndrome Burnout Tenaga Medis Covid-19 RS Andi Makkasau Kota Parepare - Awaliah Putri, Mega; Ramlan, Ramlan; Anggraeny, Rini; Hengky, Henni Kumaladewi (Jurnal Kesehatan Nusantara (JKN), 2025)
Covid-19 disease pandemic has put considerable psychological stress on frontline health care workers (health workers). Apart from being life threatening, the Covid-19 pandemic has also caused high levels of panic and anxiety around the world, especially among healthcare workers. The purpose of this study was to determine the relationship between age risk factors, number of children, working hours and work experience with the level of burnout syndrome of Covid-19 medical personnel at Andi Makkasau Hospital, Parepare City. The research method used is analytical research using a cross sectional study with Chi Square analysis. The measuring instrument used is the Maslach Burnout Inventory (MBI) questionnaire. The population and sample in this study were 35 Covid-19 medical personnel. Chi Square test results p = 0.227 is greater than = 0.05 which means Ho is accepted. Age, number of children, work experience had a p value greater than = 0.05, while working hours had a p value smaller than = 0.05. It was concluded that there was no relationship between age, number of children, and work experience on the level of burnout syndrome, but working hours had a relationship with the level of burnout syndrome of medical personnel for Covid-19 medical personnel at Andi Makkasau Hospital, Parepare City. It is hoped that the Andi Makkasau Hospital in Parepare City pays attention to medical officers who experience burnout so as not to cause a decrease in the quality of service in the workplace.